Abnormal Liver Function and Blood Coagulation Function of Coronavirus Disease 2019-Infected Pregnant Women - Wenping Sun; Jing Zhang; Hongmei Liu (Clinical and Experimental Obstetrics & Gynecology)
Background: Coronavirus disease 2019 (COVID-19) has been found worldwide since its first outbreak in December 2019. Methods: This study investigated 347 pregnant women at approximately 39 weeks’ gestation from December 2022 to January 2023, which was divided into two groups: COVID-19 positive group (COVID-19) and COVID-19 negative group (Control). We analyzed blood parameters, liver function, and coagulation parameters of pregnant women with COVID-19 infection and in the Control group. Finally, we divided pregnant women with COVID-19 into two subgroups: No medication (n = 117) and Paracetamol treatment (n = 47), and analyzed effects of paracetamol treatment on the liver and blood coagulation function in COVID-19 infected pregnant women. Results: The alanine aminotransferase (ALT), aspartate aminotransferase (AST), serum total bilirubin (TBIL), total bile acid (TBA), and lactate dehydrogenase (LDH) levels were significantly higher in pregnant women with COVID-19 than that of the control group. Elevated D-dimer, prolonged prothrombin time (PT), activated partial thromboplastin time (APTT), and low levels of fibrinogen (Fib) were observed in patients with COVID-19. There were no significant differences in the liver function between the drug treatment group and no medication group. Conclusions: COVID-19 caused abnormal liver function and blood coagulation function in pregnant women.